The Interplay of Empathy and Individualism in Support for Social Welfare Policies. Issue 2 (26th September 2019) - Feldman, Stanley; Huddy, Leonie; Wronski, Julie; Lown, Patrick
Abstract : Public support for government welfare programs is grounded in two potentially conflicting factors: a belief in individualism which undermines support for welfare assistance and the capacity for empathy which potentially enhances support. However, empathy is an expensive psychological commodity subject to pervasive up‐ and down‐regulation. This article examines the degree to which a belief in individualism affects the expression of compassionate support for a person in need among those with the capacity for empathy. In two online survey experiments, empathic ability powerfully increases support for a welfare recipient and social welfare policies when it does not conflict with individualism. But, empathic ability decreases compassion and support for government welfare among strong individualists. Evidence that individualists down‐regulate empathy for someone in need of government assistance is consistent with the conservative view that welfare promotes dependency and undermines individual agency. In contrast, charitable assistance is not associated with long‐term dependency, and we find that empathy is up‐regulated by strong individualists to generate charitable support for the same individual to whom they denied government assistance. The up‐ and down‐regulation of empathy in response to someone in need of government welfare helps illuminate the sharp divisions over social welfare policy among the American public.